Psychosocial interventions for mental health in children from broken homes: A systematic review - Rengganis, Khahla Pramesti Dwi; Eka Sari, Jayanti Dian (JOURNAL OF Mental Health Concerns, 2026)
Background: Family plays a crucial role in children’s psychological development. A “broken home,” resulting from divorce, parental death, or prolonged conflict, can disrupt emotional stability and increase the risk of mental health problems in children and adolescents. Purpose: To analyse empirical evidence regarding the impact of broken homes on children’s mental health and identify dominant psychological outcomes and protective factors. Method: A Systematic Literature Review (SLR) approach following the PRISMA protocol. Articles were retrieved from Scopus, Google Scholar, and national journals using relevant keywords. Of 231 identified articles, 7 studies published between 2018–2024 met the inclusion criteria, focusing on children and adolescents. Results: The findings showed that children from broken homes were more likely to experience anxiety (47%), depression (32%), and decreased academic performance (67%). Social support from extended family and peers, along with mindfulness-based psychosocial interventions, were found to effectively reduce psychological distress. Conclusion: Broken home conditions significantly affect children’s mental health. Strengthening social support and implementing school- and community-based mental health services are essential to promote resilience and reduce adverse outcomes. Keywords: Broken Home; Children; Mental Health.